Interrupted Time Series Versus Statistical Process Control in Quality Improvement Projects. Issue 1 (January 2016) - Andersson Hagiwara, Magnus; Andersson Gäre, Boel; Elg, Mattias
Abstract : To measure the effect of quality improvement interventions, it is appropriate to use analysis methods that measure data over time. Examples of such methods include statistical process control analysis and interrupted time series with segmented regression analysis. This article compares the use of statistical process control analysis and interrupted time series with segmented regression analysis for evaluating the longitudinal effects of quality improvement interventions, using an example study on an evaluation of a computerized decision support system.